Studi Kasus Faktor-Faktor Yang Mempengaruhi Minat Berwirausaha Pada Siswa Kelas XII Tata Boga 2 Di SMK Negeri 6 Surabaya - Fadiyah Qiyamulail Abidah; Lucia Tri Pangesthi; Sri Handajani; Romadhoni (Universitas Maritim AMNI Semarang, 2023)
The report on the career paths of alums from Public Vocational High School 6 Surabaya between 2019 and 2022 shows that alums pursuing careers as entrepreneurs are lower than those becoming employees. This study aims to determine the intrinsic and extrinsic factors and their simultaneous influence on the interest in entrepreneurship of 12th-grade students in the Culinary 2 class at Public Vocational High School 6 Surabaya. The research used a descriptive method with a quantitative approach and examined the impact of intrinsic and extrinsic factors, both individually and simultaneously, on student's entrepreneurial interests. The population of this study consisted of 30 students in the 12th-grade Culinary 2 class at Public Vocational High School 6 Surabaya. The data was collected using a validated questionnaire comprising 30 items. Meanwhile, the data analysis technique used was multiple linear regression. The results indicated that intrinsic factors did not influence student's interest in entrepreneurship. Contrarily, the extrinsic factors did have an influence. Furthermore, intrinsic and extrinsic factors simultaneously influence student's interest in entrepreneurship. Therefore, students at Public Vocational High School 6 Surabaya tend to be interested in entrepreneurship due to the encouragement they receive from their environment, including their family, community, and school. Moreover, the student's willingness and interest also played a supporting role. Thus, student's interest in pursuing careers as entrepreneurs can evolve if there is support from all parties.